2011
DOI: 10.1590/s1809-98232011000300008
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre o benefício do aparelho de amplificação sonora individual e desempenho cognitivo em usuário idoso

Abstract: OBJETIVOS: Verificar o uso efetivo do AASI pelos idosos, seus benefícios sociais e pessoais e sua relação com o desempenho cognitivo. MÉTODO: Estudo observacional, transversal, realizado no Hospital das Clínicas da UFMG, com 15 indivíduos com idade igual ou superior a 65 anos e usuários de AASI há quatro meses. Foram utilizados: QI-AASI, limiar de reconhecimento de fala e Mini-Exame do Estado Mental - Mini-Mental. Para comparação dos resultados, os sujeitos usuários de AASI foram divididos em dois grupos: Mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
2
3
0
2
Order By: Relevance
“…This result not only confirms previous studies but also what was expected by the researchers, since it has been described in both national and international literature 5,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] . The age of the individuals caused an increase in auditory thresholds, which may lead to an even more harmed speech comprehension.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result not only confirms previous studies but also what was expected by the researchers, since it has been described in both national and international literature 5,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] . The age of the individuals caused an increase in auditory thresholds, which may lead to an even more harmed speech comprehension.…”
Section: Discussionsupporting
confidence: 91%
“…This index confirms the relation between cognitive impairment and auditory sensorial restriction -which are factors that need to be taken into account in audiology evaluations. Thus, the identification of individuals with potential risk of developing cognitive alterations becomes mandatory once the early diagnosis enables the precise therapeutic intervention, avoiding -or delaying, in some cases -the beginning of dementia 38 , reducing family stress, risk of accidents, isolation and consequential harm to the older person's quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…Upon verifying effective use of PSAP by the elderly, its social benefits and their relationship with cognitive performance, researchers (24) found that patient follow-up by means of conventional tests and self-assessment questionnaires promote efficacy of PSAP use, reducing the number of patients who stop using the device because of dissatisfaction, whether due to functional or psychosocial aspects. In addition, they point out that the patient's cognitive state reveals whether there is a need for closer follow-up and specific family guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Concluíram que o uso da prótese diminuiu os efeitos da perda auditiva sobre a comunicação, pois houve diminuição da percepção do handicap auditivo e das queixas relacionadas às limitações no convívio social. Assim como descrito no estudo realizado por ÁVILA et al (2011), que o uso do AASI proporcionou benefícios sociais e pessoais e a redução da percepção do handicap auditivo na população de idosos estudada.…”
Section: Tabela 4 -Grau Deunclassified